A review on cement degradation under CO2-rich environment of sequestration projects - Abid, K.; Gholami, Raoof; Choate, P.; Nagaratnam, B. (2015)
Global warming arising from the release of greenhouse gasses into the atmosphere is one of the biggest issues attracting a lot of attention. One of the conventional problems in sequestration projects is the degradation of Portland cement due to its exposure to supercritical CO2. This paper gives a review on the laboratory work performed to understand changes in the mechanical and transport properties of cement when it is in a CO2 rich environment. The results obtained indicated that pozzolanic material could be useful in enhancing the cement resistance against CO2, although more studies are still required to confirm this conclusion.